Situações de risco biológico presentes na assistência de enfermagem nas unidades de saúde da família (USF) - Ana Carla Moreira Cardoso (Revista Latino-Americana de Enfermagem, 2010)
There is very frequent exposure to potentially contaminated material in procedures performed by nursing professionals. This exploratory and descriptive study characterizes the potential risk of biological exposure in procedures performed by nursing professionals in ten Family Health units in São Carlos-SP, Brazil. We observed 238 procedures involving potential risk of contact with biological material, in which more than 90% involved the use of needles. The average rates of adherence to standard precautions were: 27.9% hand washing prior to procedures; 41.4% use of gloves; and 88.8% adequate disposal of piercing and cutting instruments. These professionals are subject to risks similar to those which hospital workers are also subjected, because they have a high risk of blood exposure and the frequency with which they handle needles is very high.